Deep Brain Stimulation as a Tool for Improving Cognitive Functioning in Alzheimer’s Dementia: A Systematic Review - Hardenacke, Katja; Shubina, Elena; Bührle, Christian P.; Zapf, Alexandra; Lenartz, Doris; Klosterkötter, Joachim; Visser-Vandewalle, Veerle; Kuhn, Jens (Frontiers in Psychiatry, 2013)
Deep brain stimulation (DBS) is an established, in selected cases therapeutically effective, non-lesional treatment method delivering current rectangular pulses into dysfunctional brain structures via chronically implanted stimulation electrodes. DBS is a recognized method applied in movement disorders and is increasingly evaluated as a possible therapeutic option for psychiatric diseases such as refractory obsessive-compulsive disorders, Gilles de la Tourette syndrome, major depression, and substance-related addiction. Latest research indicates that DBS may be a method for improving cognitive functions in Alzheimer’s dementia (AD). Translational data in healthy and AD animals appear to support this notion. Nevertheless, many aspects remain unclear, particularly with regard to the optimal target structure. The objective of this review is to present a systematic overview regarding published research on DBS and cognitive functioning in animal and human studies as well as to provide a systematic overview of the feasibility and efficacy of the treatment. We describe three studies investigating the effects of DBS in patients with dementia, using either the fornix or the nucleus basalis of Meynert (NBM) as a target. In total, we identified 25 animal studies with 10 brain structures being targeted: fornix, NBM, anterior caudate nucleus, dorsal striatum, anterior thalamic nucleus, midline thalamic nuclei, central thalamus, lateral hypothalamus, hippocampus (entorhinal cortex, perforant path), and amygdala. Considering the wide and diverse spectrum of targets, we add to this review a supposition about possible underlying mechanisms of operation and recommendations for further research.